Does the MUI fatwa on Multi Contracts Causes Gharar? - Hamzah Rojulul Ghodi Assyarif Sumanto; Andri Nirwana AN; Muchammad Ichsan (Tazkia Islamic Finance and Business Review, 2022)
Law in Islamic syariat is focused on the realization of muamalah for humans, so that things that are opposite and contrary to benefit are definitely annulled in Islamic law, among things that are prohibited because they are contrary to benefit are muamalah behaviors that contain gharar, among transaction behaviors that are containing gharar is multi-contract multi-contract that has different laws and consequences that arise in one contract and time, this is due to uncertainty about the contract that occurs, between buying and selling or leasing contracts, in this case, and the MUI issues a fatwa regarding the rules multi-contract contracts which are justified by Islamic law, contained in fatwa no. 27 of 2002 concerning buying and selling leases, this research will examine the fatwa, whether the fatwa has the opportunity to cause gharar or not? , the method used in this research is a qualitative method by analyzing the content of the fatwa even though testing it with gharar theory which leads to the conclusion that the fatwa dsnmui no.27 of 2002 has no chance of causing gharar. Keywords: Fatwa , Hybrid contract, Gharar, Muamalah